2004
DOI: 10.1089/1076327041348464
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of Functional Tendon

Abstract: Surgical tendon repair is limited by the availability of viable tissue for transplantation. Because of its relatively avascular nature, tendon is a prime candidate for engineered tissue replacement. To address this problem, cells isolated from rat Achilles tendon were grown to confluence in culture and allowed to self-assemble into a cylinder between two anchor points. The resulting scaffold-free tissue was composed of aligned, small-diameter collagen fibrils, a large number of cells, and an excess of noncolla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
129
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(131 citation statements)
references
References 33 publications
1
129
0
Order By: Relevance
“…The rationale of this approach is based on the fact that cells can create their own tissue-specific ECM, bypassing the need for artificial devices and their shortfalls. The first in vitro study demonstrated that such cellular assemblies resemble the nonlinear behaviour of immature tendons [440]. Using rat TSCs, a neotendon tissue was formed that after eight weeks in a rat patellar tendon defect model showed marked improvement in histological scores, tissue alignment and mechanical properties, as compared to naturally healed control [441].…”
Section: Tissue Engineering By Self-assembly Therapiesmentioning
confidence: 99%
“…The rationale of this approach is based on the fact that cells can create their own tissue-specific ECM, bypassing the need for artificial devices and their shortfalls. The first in vitro study demonstrated that such cellular assemblies resemble the nonlinear behaviour of immature tendons [440]. Using rat TSCs, a neotendon tissue was formed that after eight weeks in a rat patellar tendon defect model showed marked improvement in histological scores, tissue alignment and mechanical properties, as compared to naturally healed control [441].…”
Section: Tissue Engineering By Self-assembly Therapiesmentioning
confidence: 99%
“…In these cases, the tendon is recognized to be a prime candidate for engineeredtissue replacement. 21 However, so far, few studies have been done on rotator cuff tendon regeneration by means of in situ tissue engineering and in vitro bioengineering of tendons as compared to the extensive work on bone and cartilage. 6,14,[22][23][24][25] This previous literature review, showed the necessity for future studies in this area, and, therefore, an in vitro study was performed by isolating tenocytes from the rotator cuff of normal and GC-treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…9 In the present study, cells derived from tendons were used and were characterized by means of cell morphology and ECM protein production as performed in many other studies. 12,13,21,23,26,29,30,33,35 Moreover, in our study in order to maintain the phenotype we used the explant technique, in which cells are permitted to grow from small fragments of tissue instead of enzymatic digestion that affects cell membrane and destroys the cell-cell and cell-matrix relationship. 36 It is reported that the explant technique is best to determine the phenotype of the cells derived from tendons.…”
Section: Discussionmentioning
confidence: 99%
“…This technique involves construction of whole body tissues in the laboratory, and their inplantation into patients. Several studies have demonstrated engineering whole tendons in such a manner (Calve, Dennis, Kosnik, Baar, Grosh, & Arruda, 2004;Cao, Liu, Wei, Xu, Cui, & Cao, 2006). These strategies are currently at an early stage of development and their full impact needs to be the focus of intense research.…”
Section: Genes Used For Treating Sports Injuriesmentioning
confidence: 99%